Providing detailed information about latent tuberculosis and compliance with the PPD test among healthcare workers in Israel: A randomized controlled study - Danielle Taubman; Nava Titler; Hana Edelstein; Mazen Elias; Walid Saliba (Springer, 2019)
Background: The compliance of screening for latent tuberculosis (TB) with the tuberculin purified protein derivative (PPD) test is very low among healthcare workers (HCWs) in Israel. Methods: This randomized controlled study uses the Health Belief Model (HBM) as a conceptual framework to examine whether providing more information about latent TB and the PPD test increases the response rate for PPD screening among HCWs. All candidate HCWs for latent TB screening were randomly allocated to one of the following two invitations to perform the PPD test: regular letter (control group, n = 97), and a letter with information about latent TB and the PPD test (intervention group, n = 196). Results: 293 HCWs were included (185 nurses, and 108 physicians). Overall, 36 (12.3%) HCWs were compliant with the PPD test screening. Compliance with PPD testing in the intervention group was not statistically different from the control group, RR 0.87 (95% CI, 0.46-1.65). Conclusions: Compliance for latent TB screening is low among HCWs in northeastern Israel. Providing detailed information about latent TB was not associated with increased test compliance. Understanding existing disparities in screening rates and potential barriers to latent TB screening among HCWs is important in order to move forward and successfully increase screening rates.